BUSINESS ANALYSIS AND MARKETING OF TILAPIA CASE FLOATING NET CAGES IN ALANG RIVER VILLAGE, KARANG INTAN DISTRICT, BANJAR REGENCY, SOUTH KALIMANTAN PROVINCE - Tri Dekayanti; Irma Febrianty; Mira Annisa (Fish Scientiae, 2022)
Alang river Village, Karang Intan District is a village that has a lot of potential in the field of fisheries, especially in the floating net cage media with the commodity of Tilapia which is commonly used by the community, this fish cultivator business is a source of income in the village by utilizing the river that stretches around Alang river village. The problem that occurs in the Jasmine Fish Cultivator Group is the death of the fish which results in many losses and problems in access to fish marketing outside the South Kalimantan area. The purpose of this research was to analyze the feasibility of the business and to analyze the marketing of rearing tilapia in POKDAKAN Melati floating net cages in Sungai Alang village. The method this research is Primary, Secondary, Interview, Observation, Snowball Sampling, and Documentation Methods. The results of this research indicate that the business run by POKDAKAN Melati is feasible and profitable to be developed with profit the average per month is Rp. 5,309,863.2 within a repayment period of 0.46 years or 5 months 16 days, with a total NPV of 7% of Rp. 418,052,002, Net BCR 7% of 1.35% and IRR value of 136.74% Meanwhile, for the marketing channels, there are 2 marketing channels, namely semi-direct channels and indirect channels with the amount of Farmer Share analysis of 78% which can be said to be efficient. Desa Sungai Alang Kecamatan Karang Intan merupakan desa yang memiliki banyak pontensi dibidang perikanan khusus nya pada media Karamba Jaring Apung dengan komoditi Ikan Nila yang biasa digunakan masyarakat, usaha pembudidaya ikan ini merupakan sumber penghasilan yang ada di desa tersebut dengan memanfaatkan sungai yang membentang disekitaran desa sungai alang. Permasalahan yang terjadi pada Kelompok Pembudidaya Ikan Melati adalah kematian ikan yang mengakibatkan banyaknya kerugian yang dialami dan permasalahan akses pemasaran ikan untuk luar daerah Kalimantan Selatan. Tujuan penelitian ini ialah menganalisis kelayakan usaha dan menganalisis pemasaran pembesaran ikan nila pada POKDAKAN Melati Karamba Jaring Apung Desa Sungai Alang. Metode dalam penelitian ini ialah Primer, Sekunder, Wawancara, Observasi, Snowball Sampling, dan Dokumentasi. Hasil dari penelitian menunjukkan bahwa usaha yang dijalankan POKDAKAN Melati layak dan menguntungkan untuk dikembangkan dengan hasil keuntungan rata-rata per bulan nya sebesar Rp. 5.309.863,2 dalam kurun waktu pengembalian 0,46 tahun atau 5 bulan 16 hari, dengan jumlah NPV 7% sebesar Rp. 418.052.002 , Net BCR 7% sebesar 1,35 % dan nilai IRR 136,74% sedangkan untuk salurannya pemasaran didapatkan 2 saluran pemasaran yaitu saluran semi langsung dan saluran tidak langsung dengan jumlah analisis Farmer Share 78% yang mana dapat dikatakan efisien.